Ginger (Zingiber officinale Roscoe) as a nutraceutical: Focus on the metabolic, analgesic, and antiinflammatory effects - Pagano, Ester (2021)
Ginger (from the rizhome of Zingiber officinale Roscoe) has been widely used in ethnomedicine for the cure of several ailments. Main active ingredients include phenolic compounds named gingerols. In modern phytotherapy, ginger preparations are predominantly used to counteract nausea and vomiting in pregnant women. However, a number of other pharmacological actions of potential therapeutic interest, which might broaden the spectrum of its clinical use, have been reported. This focused review aims at giving a shot on the antinflammatory, analgesic, and metabolic actions of Zingiber officinale preparations, with a discussion on the clinical applications in knee osteoarthritis, dysmenorrhea, type-2 diabetes, hyperlipidemia, overweight, and obesity.